Avaliação da expressão de microRNAs e proteínas como biomarcadores de diagnóstico em carcinoma epidermoide de língua - Có, Anna Clara Gregório (2023)
Oral squamous cell carcinoma (OSCC) is the 16th most commonly diagnosed form of cancer globally, with a higher prevalence in the tongue compared to other areas of the oral cavity. However, the lack of effective biomarkers for diagnosis, especially for precancerous lesions, poses a limitation, as visual or histological examination cannot predict the progression of dysplastic lesions, making it difficult to determine whether they will develop into cancer or return to normal epithelium. In this context, the present research aims to investigate molecular targets that may indicate the irreversible transformation of these cells, to provide a basis for broader studies aimed at using these targets as biomarkers for early OSCC diagnosis. To achieve this goal, this experimental study addressed the evaluation of the expression of a panel of microRNAs and proteins in tumour tissues and adjacent tumour-adjacent epithelium obtained from patients with tongue squamous cell carcinoma and oral epithelium from healthy individuals. Additionally, the research explored the association between these biomarkers, seeking to determine their potential application as diagnostic biomarkers for tongue squamous cell carcinoma. A total of 75 cases of tongue squamous cell carcinoma and adjacent tumouradjacent epithelium were included in the study, and the expression of the proteins survivin, Bcl-2, PLK1, p16, p40, p63, EGFR, and cyclin D1 was analysed by immunohistochemistry. The analysis of the microRNA panel's expression involved 31 samples of tongue squamous cell carcinoma, 10 samples of healthy gingival tissue, and 10 samples of serum from healthy individuals, as well as 7 samples of serum from patients diagnosed with OSCC, using the RT-qPCR technique. In silico analysis by bioinformatics validated the findings related to the expression of differentially expressed microRNAs in the sample group. The results showed differences in the expression of miRNA-31-5p (p<0.001) and miRNA-21-5p (p=0.001) in tumour samples compared to control samples. Significant differences were not observed in the expression of miRNA-24-3p, while miRNA-542-3p and 196a-5p were not detected in the sample group. No significant difference was observed in the expression of miRNAs in serum samples. The assessment of the diagnostic potential of microRNAs included ROC curve analysis, which revealed that miR-21-5p had an area under the curve (AUC) of 0.803, while miR-31-5p obtained an AUC of 0.777. The results also identified differential expression among the proteins survivin, PLK1, and p63, all of which showed increased expression in tumour tissue. Additionally, a correlation was observed between the expression of miR-21-5p and the protein p40 (chi-square: p=0.047; Spearman correlation: r=0.402; p=0.023). In conclusion, the results suggest that miR-21-5p and miR-31-5p may be potential diagnostic biomarkers for tongue squamous cell carcinoma, providing a foundation for further exploration for large-scale studies to explore miRNA-protein correlations, considering the site specificity of miRNAs.